PENGARUH PENGGUNAAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN BERBASIS AKRUAL DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Misrawati Madukala Madukala; Nasruil Nasrul; Sri Wiyati Mahrani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2018)
Effect of the use of accrual-based financial management information system and work satisfaction on employee performance of the regional financial and asset management agency of konawe utara regency. This study aims to find out and examine: (1) effect of accrual-based financial management information system (simda) and work satisfaction on the performance of bpkad north konawe district employees, (2) effect of accrual-based financial management information systems (simda) on the performance of bpkad employees in north kawe regency, (3) effect of job satisfaction on the performance of bpkad north konawe district employees.This study used a sample of 44 respondents. The analysis technique used is descriptive statistical analysis techniques and inferential statistics. The analysis used is multiple linear regression using the spss program package ver. 23.0The results showed that: (1) the use of accrual-based financial regional management information system (simda) and work satisfaction had a significant effect on the performance of bpkad north konawe district employees, (2) the use of accrual-based financial regional management information (simda) systems had a significant effect on performance bpkad north konawe district employee, (3) work satisfaction has a significant effect on the performance of bpkad north konawe district employees.Keywords:management information system, work satisfaction, performance of staff